Biodiversity in arid fruit crops: A review (Indian Journal of Arid Horticulture, 2025)
Hot arid regions are confronted with climatic adversities besides lack of sufficient  irrigation water availability. However, there are numerous fruit species which have  inbuilt mechanism to sustain under inhospitable edaphoclimatic condition with  available rainfall. The fruits like ber, deshi bordi, jhar ber, khejri, ker, pilu, etc. have  been grown successfully under natural condition without irrigation. In some pockets  (10-12%), where irrigation water is available either by canal system or underground  tubewel, cash crops like date palm, pomegranate, fig, aonla, citrus fruits, etc. are  some of the successful ventures by the farmers. The available natural biodiversity  present in these fruit crops have been successfully employed to develop high yielding  improved varieties mostly by selection from seedling population. The development of  clonal propagation techniques enabled perpetuation of developed varieties without  the loss of original quality. The strengthening of R&D in ICAR institutes and SAUs  further helped in the development of location specific agro-techniques, which led to  yield enhancement and post-harvest value addition in typical arid fruit crops. This  review article highlights the availability of biodiversity and varietal development in  arid fruit crops.
Keywords: Biodiversity; arid fruits; selection; variability